Electrochemistry of single entities and ensembles of metal-based nanoparticles - Xie, RC (2021)
This thesis aims at both electrochemically investigating mainly at the single entity level the physicochemical properties of metal-based nanoparticles and seeking to study unusual electrochemical activity of metal nanoparticle ensembles by using mainly an optical approach. Three experimental stages are presented accordingly: